2018
DOI: 10.1111/rec.12870
|View full text |Cite
|
Sign up to set email alerts
|

Amendments fail to hasten biocrust recovery or soil stability at a disturbed dryland sandy site

Abstract: In most drylands, biological soil crusts (biocrusts), an assemblage of lichens, bryophytes, fungi, green algae, and cyanobacteria, are critical to healthy ecosystem function. However, they are extremely sensitive to disturbance and attempts to facilitate their recovery have had variable success. In this study, we applied soil amendments designed to improve soil surface stability and accelerate biocrust recovery on an area disturbed by oil/gas exploration vehicles. Treatments included: (1) control (one time wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…EPS may also occur in a variety of morphologies and configurations within the soil matrix, dependent on species and conditions (Rossi, Mugnai, & De Philippis, 2017 a abundance) and functional stabilization (surface roughness and aggregate stability) may be ameliorated with the use of stabilizers in the short term ( Figure 6). Other studies have found neutral to improved cyanobacterial growth when simultaneously inoculated with stabilizers (Chandler et al, 2018;Davidson et al, 2002;Park, Li, Jia, & Hur, 2014;Peng et al, 2017), and in plots sampled for this study, microbiotic chlorophyll was marginally greater in plots with both biocrust and stabilizer. More studies are needed to determine the mechanisms by which soil-stabilizing amendments may facilitate microbiotic growth, such as by anchoring inoculum (Ballesteros, Ayerbe, Casares, Cañadas, & Lorite, 2017), providing microsubstrate for improved growth (Zaady, Katra, Barkai, Knoll, & Sarig, 2016), or improving water status or nutritional conditions (Park et al, 2016).…”
Section: Biocrust Restoration and Erosion Processessupporting
confidence: 50%
See 4 more Smart Citations
“…EPS may also occur in a variety of morphologies and configurations within the soil matrix, dependent on species and conditions (Rossi, Mugnai, & De Philippis, 2017 a abundance) and functional stabilization (surface roughness and aggregate stability) may be ameliorated with the use of stabilizers in the short term ( Figure 6). Other studies have found neutral to improved cyanobacterial growth when simultaneously inoculated with stabilizers (Chandler et al, 2018;Davidson et al, 2002;Park, Li, Jia, & Hur, 2014;Peng et al, 2017), and in plots sampled for this study, microbiotic chlorophyll was marginally greater in plots with both biocrust and stabilizer. More studies are needed to determine the mechanisms by which soil-stabilizing amendments may facilitate microbiotic growth, such as by anchoring inoculum (Ballesteros, Ayerbe, Casares, Cañadas, & Lorite, 2017), providing microsubstrate for improved growth (Zaady, Katra, Barkai, Knoll, & Sarig, 2016), or improving water status or nutritional conditions (Park et al, 2016).…”
Section: Biocrust Restoration and Erosion Processessupporting
confidence: 50%
“…Many of the recorded successes correspond with periods of greater moisture availability, such as Chen et al (2006) who implemented large-scale continuous irrigation. Other studies have found little difference from natural recovery or outright failure of establishment (Chandler, Day, Madsen, & Belnap, 2018;Young, Bowker, Reed, Duniway, & Belnap, in press). Given publication bias towards significant results in ecology (Møller & Jennions, 2001), it is likely that more unsuccessful biocrust restorations exist than are reported in the literature.…”
mentioning
confidence: 91%
See 3 more Smart Citations